General health and dısabılıty status: a comparatıve study between nursıng home resıdents and elderly lıvıng at theır own homes - (:unkn) unknown (My University, 2012)
Giriş: Bu araştırmanın amacı huzurevinde ve evde yaşayan yaşlılarda genel sağlık ve yeti yitimi durumunun karşılaştırılmasıdır. Gereç ve Yöntem: Bu çalışma, 2000 yılının Temmuz ayında, Ankara'daki iki huzurevi ve üç köyde, 60 yaş ve üzeri 367 kişiye uygulanmıştır. Anket formunda incelenenlere tanımlayıcı sorular, Genel Sağlık Anketi -12 (GHQ-12), Kısa Yeti Yitimi Anketi (BDQ) ve Yaşlılar İçin Depresyon Ölçeği (GDS) uygulanmıştır. Bulgular: Bu çalışmada huzurevi ile evde yaşayan yaşlılar arasında GHQ ve BDQ puanları arasında istatistiksel olarak anlamlı fark saptanmıştır (p<0.05). Her iki skorun da huzurevinde yaşayan yaşlılarda daha yüksek olduğu görülmüştür. Huzurevinde yaşayanlarda yüksek BDQ puanı için kadın olmak, kronik hastalığın olması ve depresyonda olmak risk faktörü iken, yüksek GHQ-12 için depresyonun olması risk faktörüdür (p<0.05). Sonuç: Bu çalışmada huzurevinde yaşayan yaşlılarda GHQ-12 ve BDQ skorları evde yaşayan yaşlılara göre daha yüksek saptadık. Huzurevinde yaşayan yaşlılarda evde yaşayanlara göre GHQ- 12 ve BDQ tarama testlerinin daha sıklıkla kullanılması önerilmektedir.

Introduction: The objective of this study is to compare the general health and disability status of the elderly living in nursing homes or in their own homes. Materials and Method: The study was carried out in July, 2000 on 367 elderly, aged ≥60, living in two nursing homes in Ankara and at their own houses in three villages of Gölbafl›. A survey form including descriptive questions, the General Health Questionnaire (GHQ-12), the Brief Disability Questionnaire (BDQ), and the Geriatric Depression Scale (GDS) was administered to participants. Results: There was a statistically significant difference in the GHQ-12 and BDQ mean scores between those living in nursing homes and at home (p<0.05). Scores were higher for those living at nursing homes for both conditions. For those living in nursing homes, the risk factors for increased BDQ scores were being female, suffering from a chronic disease and to having a depression disorder. The risk factor for GHQ-12 was having a depression disorder (p<0.05). Conclusion: We found that the GHQ-12 and BDQ scores were higher for those living in nursing homes compared to those living at home. The GHQ-12 and BDQ should be used as screening tools for the early diagnosis of psychological problems, especially for those living in nursing homes.
Genel sağlık ve yeti yitimi durumu: huzurevinde ve evde yaşayanlarda karşılaştırılmalı bir çalışma
Keywords: Cerrahi